Nivolumab switch maintenance therapy after tyrosine kinase inhibitor induction in metastatic renal cell carcinoma: a randomized clinical trial by the interdisciplinary working group on renal tumors of the German cancer society (NIVOSWITCH; AIO-NZK-0116ass) - Grünwald, Viktor; Ivanyi, Philipp; Zschäbitz, Stefanie; Wirth, Manfred; Staib, Peter; Schostak, Martin; Dargatz, Philip; Müller, Lothar; Metz, Michael; Bergmann, Lothar; Steiner, Thomas; Welslau, Martin; et al. (European urology, 2023)
Background - The role of immune checkpoint inhibitor (ICI) maintenance therapy in metastatic renal cell carcinoma (mRCC) is undefined. - Objective - To determine whether switch maintenance therapy with nivolumab improves clinical outcomes in patients with mRCC with tyrosine kinase inhibitor (TKI) sensitivity. - Design, setting, and participants - This open-label phase 2 trial randomized patients with a partial response or stable disease after 10-12-wk TKI induction therapy to either TKI or nivolumab maintenance. Key inclusion criteria were measurable disease, clear cell histology, Eastern Cooperative Oncology Group performance status (ECOG PS) 0-2, and adequate organ function. - Intervention - Intravenous nivolumab 8 × 240 mg every 2 wk, followed by 480 mg every 4 wk or sunitinib 50 mg (4-2 regimen) or pazopanib 800 mg once daily orally. - Outcome measurements and statistical analyses - The primary endpoint was overall survival (OS). Secondary endpoints were the objective response rate (ORR; Response Evaluation Criteria in Solid Tumors v1.1), progression-free survival (PFS), safety (Common Terminology Criteria for Adverse Events v4.03), and patient-reported outcomes (Functional Assessment of Cancer Therapy Kidney Symptom Index). The Kaplan-Meier method, two-sided log-rank tests, and Cox regression models were used for statistical analysis. - Results and limitations - Maintenance therapy was nivolumab for 25 patients (51.0%) and TKI for 24 (48.9%). The median age was 65 yr (range 35-79). Nine patients (18.4%) were female, 31 (63.3%) had ECOG PS of 0, and 15 (30.6%) had favorable risk. OS data are immature (17 deaths, 34.7%). The ORR was 20.0% (n = 5) for nivolumab and 52.2% (n = 12) for TKI. PFS was worse with nivolumab (hazard ratio 2.57, 95% confidence interval 1.36-4.89; p = 0.003). Grade ≥3 adverse events occurred in 14 patients (56.0%) with nivolumab and 17 (70.8%) with TKI. A major limitation is early termination of our study. - Conclusions - TKI treatment achieved superior ORR and PFS in comparison to nivolumab maintenance therapy. Our data do not indicate a role for nivolumab switch maintenance in mRCC. - Patient summary - Patients with metastatic kidney cancer who experienced a tumor response or disease stabilization after a short period of targeted treatment with a tyrosine kinase inhibitor did not benefit from a switch to the immunotherapy drug nivolumab. Patients who continued their original treatment achieved better responses and a longer time without disease progression. This trial is registered on EudraCT as 2016-002170-13 and on ClinicalTrials.gov as NCT02959554.
Gesehen am 02.02.2024
Online verfügbar 26 September 2023, Version des Artikels 13 November 2023